CONTROL, REACTION SPEED, AND THEIR CONTRIBUTION TO THE ACCURACY OF RECEPTION FROM SPIKE SERVE AND COURT DEFENSE FROM POSITION (4) AMONG PREMIER LEAGUE VOLLEYBALL PLAYERS - Asst. Prof. Dr. Amjad Hamed Badr (Proximus Journal Publishing, 2025)
Using a survey methodology and correlational analysis, the researcher used the descriptive method. With eight clubs and fourteen players per club competing in the Iraqi Premier League, the research population was purposefully chosen to include Premier League volleyball players for the 2024–2025 season. To get results, the researcher used the court defense exam, the visual selective attention test, and the spike serve reception accuracy test. The Statistical Package for the Social Sciences (SPSS) was then used to statistically process the data
Keywords: Control; Reaction Speed; Reception